Identifying the factors affecting in the Intentions to continue using of the government social media - جبار عبد العظيم دريفش; جلود قاسم متعب (Journal of Economics and Administrative Sciences, 2017)
Abstract Social media has thrived recently and public organizations at Thi-Qar governorate across different levels are experimenting with launching government social media (GSM) to facilitating two-way interactions between the government and its citizens. Both scholars and practitioners are focusing on understanding the key success factors related to the create of GSM. This study aimed to identify the key success factors by exploring the formation mechanism of individuals’ continuous usage intention. Through the theoretical perspective of the uses and gratifications theory. We identify the gratification factors that stimulate users’ continuance intention toward GSM. Furthermore, we draw upon the stimulus–organism–response framework to develop a model for exploring the effects of gratification factors on individuals’ online experiential states and their continuance intention. Data from 152 undergraduate students were used for construct validation with a confirmatory factor analysis, which revealed an eight-factor structure and explained 79% of the total variance. The results indicated that usage continuance intention is in part determined by gratification factors. Furthermore, the associations among gratification factors and users’ continuance intention may be mediated by the sense of belonging and flow experience. Based on these findings, we suggest that future studies in this area by Focusing more on gratification factors and on the individuals online experiential states as anteceded to the continuous usage intention.